Les relations de travail au Devoir à l’épreuve de l’affirmation collective des journalistes - François Demers (Communication)
Between the landmark events marked by the arrival of Claude Ryan in 1964 as editor of the Montreal newspaper Le Devoir and the crisis in the summer of 1993 under Lise Bissonnette, the industrial relations at the daily were profoundly influenced by a movement of collective affirmation among the French speaking journalists in the province of Quebec. At key moments, the unionized journalists of Le Devoir pressured the editors into reestablishing a balance between what they perceived as the two fundamental dimensions of the newspaper: a profitable business and a “cultural institution.”